The diagnosis of asthma and exercise-induced bronchospasm in division I athletes - Millward, D.; Paul, S.; Brown, M.; Porter, D.; Stilson, M.; Cohen, R. (Clinical Journal of Sport Medicine, 2009)
The article presents a study that determines the accuracy of clinically diagnosed exercise-induced bronchospasm (EIB) as well as asthma among athletes from National Collegiate Athletic Association Division I students in the U.S. Study shows that mean values of exhaled nitric oxide (eNO) were different across subject groups defined by the status of treatment. This result is said to have provided further evidence of supporting the need for objective testing to efficiently diagnose EIB.